2006
DOI: 10.1007/s11416-006-0009-x
|View full text |Cite
|
Sign up to set email alerts
|

Malware Pattern Scanning Schemes Secure Against Black-box Analysis

Abstract: As a general rule, copycats produce most of malware variants from an original malware strain. For this purpose, they widely perform black-box analyses of commercial scanners aiming at extracting malware detection patterns. In this paper, we first study the malware detection pattern extraction problem from a complexity point of view and provide the results of a wide-scale study of commercial scanners' black-box analysis. These results clearly show that most of the tested commercial products fail to thwart black… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 17 publications
0
54
0
2
Order By: Relevance
“…Their work presents a strong mathematical basis to define different types of behavior and is an extension of a previous work that was only able to handle sequences of bytes [8]. The limiting factor is that their new approach requires the malware's source code, which is sometimes difficult to obtain.…”
Section: Related Workmentioning
confidence: 99%
“…Their work presents a strong mathematical basis to define different types of behavior and is an extension of a previous work that was only able to handle sequences of bytes [8]. The limiting factor is that their new approach requires the malware's source code, which is sometimes difficult to obtain.…”
Section: Related Workmentioning
confidence: 99%
“…Filiol [26] address the problem that commercially available anti-viruses are not resistant against black-box analysis. He suggested generating multiple sub-signatures that are randomly selected from a longer signature.…”
Section: Related Work On Automatic Signature Generation (Asg)mentioning
confidence: 99%
“…Various techniques have been proposed to derive malware signatures automatically, including among others: vulnerability-based signatures [1]; payload-based signatures ( [7]; [19]); content sifting [17]; semantic-aware signatures [21]; The Amd algorithm [2]; Honeypot-based signatures ([8]; [15]; [18]), and polymorphic content-based signatures [14] [26]. These studies examine code by matching and analyzing the distribution of string patterns in communication packets; classifying unsuccessful connections; and modeling invariant code structures.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that above 15% of the files in the KaZaA network contained malicious code 2 . Thus, we assume that the percentage of malicious files in real life is about or less than 10%, but we also consider other possible percentages.…”
Section: Introductionmentioning
confidence: 99%